Total compensation and benefits that influence employees performance: in a view of foreign worker / Nurulfaizzati Aminah Ahmad Arsani - Ahmad Arsani, Nurulfaizzati Aminah (2007)
The purpose of this study is to determine the relationship between Total Compensation and Benefits influences Employees Performance in a view of Foreign Worker at Venture Ges Manufacturing Services (M) SDN. BHD. Venture Ges Manufacturing Services (M) SDN.BHD. are one of the manufacturing company that employed almost more than 500 foreign worker at Senai, Johor This study used the descriptive study to describe the foreign workers of Venture Ges Manufacturing Services (M) SDN. BHD. The targeted population is 270 foreign workers of Venture Ges Manufacturing Services (M) SDN. BHD. and the sample in this study covered 159 respondent from a total population. The sample was selected through simple random sampling techniques. Primary data was collected through uses of questionnaires. All the data in this research was analyze by using Descriptive analysis, Reliability Testing, Pearson Correlation analysis and Multiple Regression analysis. Based on the findings obtain from descriptive analysis on the demographic profiles, it shows that most of the foreign worker are about 31 years and above. Next, female worker are the highest respondent that male worker and most of the foreign worker are from Nepal followed by Bangladesh. Not only that, based on the working experience of the foreign worker, most of them have experience in Venture Ges Manufacturing Services (M) SDN. BHD around 6 to 10 years and most of them only earned RM 0 until RM 1000. Data findings from Pearson Correlation analysis shows that all independent variables which pay, promotion, bonuses and benefits are significantly related to employee performance. Moreover, bonuses and benefits is the most related variable related towards employee performance because the correlation is moderate compare than pay and promotion which are weak. Finally, based on the regression models, the most influences element in total compensation and benefits influence employee performance is bonuses and benefits with the highest Beta Value